Perbandingan Hasil Belajar Kimia Dalam Pembelajaran Blended Learning Menggunakan Media Edmodo Dengan Whatsapp Siswa Kelas X IPA SMAN 7 Mataram - Hayati, Nur; Muntari, Muntari; Muti’ah, Muti’ah (FKIP University of Mataram, 2024)
This study aims to determine the differences in chemistry learning outcomes in blended learning using Edmodo media with Whatsapp class X students on electrolyte and nonelectrolyte solutions. This research is a Quasi Experimental Design research (quasi-experiment). The research design used in this study was a Quasi Experimental Design, namely the Non-Equivalent Control Group Design. Sample selection using purposive sampling technique. The research sample is experimental class I (X IPA 1) which applies blended learning using Edmodo media and experimental class II (X IPA 2) which applies blended learning using whatsapp media. The data collection technique used is a test instrument for understanding concepts (pretest and posttest) in the form of multiplechoice questions. Test the hypothesis in this study using the t-test. The results of the statistical test t-test tcount at a significant level of 5% shows tcount (2.43) > ttable (1,669) which means Ha is accepted and Ho is rejected. This shows that there is a significant difference in blended learning between using edmodo and whatsapp media in improving chemistry learning outcomes, where blended learning using Edmodo media is better in improving students' chemistry learning outcomes